EXAMINING THE IMPACT OF REGULAR YOGIC EXERCISES ON MENTAL HEALTH OF SPORTSPERSONS RECOVERING FROM INJURIES (International Journal of Food and Nutritional Sciences, 2025)
Sports-related injuries are an unavoidable reality for athletes, often disrupting their training routines, competitive schedules, and overall performance. While physical rehabilitation is a critical component of recovery, the journey back to full fitness involves more than just healing the body—it requires addressing the mental and emotional challenges that accompany injury. In recent years, yoga has emerged as a powerful complementary therapy for athletes recovering from sports-related injuries. Combining physical postures, breathing techniques, and mindfulness practices, yoga offers a holistic approach to rehabilitation that goes beyond traditional methods. It not only aids in restoring physical strength, flexibility, and balance but also promotes mental resilience, emotional well-being, and stress management. This study explores the multifaceted benefits of yoga in sports injury recovery, highlighting its potential to accelerate healing, prevent re-injury, and support athletes in regaining their peak performance. The study was conducted by using a standard methodology and the data collection was done through a survey. All the data was subjected to statistical treatment using SPSS 18.0 software. The study results show that by integrating yoga into rehabilitation programs, athletes can experience a more comprehensive and sustainable recovery process, ensuring they return to their sport stronger, both physically and mentally.